2005
DOI: 10.1002/jbm.a.30427
|View full text |Cite
|
Sign up to set email alerts
|

Development of an infection‐resistant bifunctionalized Dacron biomaterial

Abstract: A novel infection-resistant biomaterial was created by applying the antibiotic Ciprofloxacin (Cipro) to a recently developed bifunctionalized polyethylene terephthalate ("polyester," Dacron) material using textile-dyeing technology. Dacron was modified via exposure to ethylenediamine (EDA) to create amine and carboxylic acid sites within the polymer backbone. Cipro was applied to the bifunctionalized Dacron construct under varied experimental conditions, with resulting antimicrobial activity determined via zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
1
24
1
Order By: Relevance
“…Additional research by our group has shown Cipro release with subsequent antimicrobial activity to persist for Ͼ40 days. 37 This sustained release is comparable to that observed with the pad-heating processes on unmodified Dacron. 42 The reduced heat involved in this pad/autoclave technique also preserves the functional groups on the material surface, thereby permitting subsequent protein binding using crosslinkers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Additional research by our group has shown Cipro release with subsequent antimicrobial activity to persist for Ͼ40 days. 37 This sustained release is comparable to that observed with the pad-heating processes on unmodified Dacron. 42 The reduced heat involved in this pad/autoclave technique also preserves the functional groups on the material surface, thereby permitting subsequent protein binding using crosslinkers.…”
Section: Discussionsupporting
confidence: 80%
“…Because the amine and carboxylic acid groups generated by EDA exposure render the Dacron surface more hydrophilic, a modified dyeing technique (pad/autoclaving) was examined. 37 C-EDA segments (3 ϫ 5 cm) were prepared as previously described. Segments were then placed into a Cipro "dyebath" that was set up as follows: liquor ratio (ratio of water weight to material weight) ϭ 20:1, percent antibiotic on the weight of fabric (% owf) ϭ 5%, pH ϭ 8.0, dyeing time ϭ 2 h, and dyeing temperature ϭ 70°C.…”
Section: Application Of Antibiotic Onto C-eda Using Textile Dyeing Tementioning
confidence: 99%
“…This results in reducing the durability of PET in implants and other long-term biomedical applications. Even with these limitations, many studies have demonstrated immobilization of active biomolecules [5,6,16,19,21,22,[24][25][26]. These studies have also showed improved hemocompatibility [6,19,21], infection resistance [5,[24][25][26] and cell adhesion [22].…”
Section: Introductionmentioning
confidence: 98%
“…Following the pioneering work of Gagliardi [20], which described the principles and strategies for imparting antimicrobial activities into fibrous materials, various biocidal agents, including antibiotics [21][22][23], metal ions [24], quaternary ammonium salts [25][26][27], phosphonium compounds [27,28], N-halamines [29,30], etc., have been incorporated into fibrous materials. The antimicrobial activities and mechanisms of these agents differ considerably.…”
Section: Introductionmentioning
confidence: 99%